The concept of ‘logic’ and ‘logical’ in the official documents of the Pope Benedict XVI in comparison with the approach present in John Paul II encyclicals - Lapis, Włodzimierz (Investigationes Linguisticae, 2016)
The article discusses the meaning of the words ‘logic’ and ‘logical’ as used by Pope Benedict XVI in the Encyclicals and Apostolic Exhortations. The approach of Benedict XVI is then compared with that of Pope John Paul II (as analyzed in Lapis (2011)).